Influenza virus infection exacerbates gene expression related to neurocognitive dysfunction in brains of old mice - Wenxin Wu; Jeremy S. Alexander; J. Leland Booth; Craig A. Miller; Jordan P. Metcalf; Douglas A. Drevets (Immunity & Ageing, 2024)
Abstract Background Age > 65 years is a key risk factor for poor outcomes after human influenza infection. Specifically, in addition to respiratory disease, non-neurotropic influenza A virus (IAV) causes neuro-cognitive complications, e.g. new onset depression and increases the risk of dementia after hospitalization. This study aimed to identify potential mechanisms of these effects by determining differences between young and old mice in brain gene expression in a mouse model of non-neurotropic IAV infection. Methods Young (12 weeks) and old (70 weeks) C57Bl/6J mice were inoculated intranasally with 200 PFU H1N1 A/PR/34/8 (PR8) or sterile PBS (mock). Gene expression in lung and brain was measured by qRT-PCR and normalized to β-actin. Findings were confirmed using the nCounter Mouse Neuroinflammation Array (NanoString) and analyzed with nSolver 4.0 and Ingenuity Pathway Analysis (IPA, Qiagen). Results IAV PR8 did not invade the central nervous system. Young and old mice differed significantly in brain gene expression at baseline and during non-neurotropic IAV infection. Expression of brain Ifnl, Irf7, and Tnf mRNAs was upregulated over baseline control at 3 days post-infection (p.i.) only in young mice, but old mice expressed more Ifnl than young mice 7 days p.i. Gene arrays showed down-regulation of the Epigenetic Regulation, Insulin Signaling, and Neurons and Neurotransmission pathways in old mice 3 days p.i. while young mice demonstrated no change or induction of these pathways at the same time point. IPA revealed marked baseline differences between old and young mice. Gene expression related to Cognitive Impairment, Memory Deficits and Learning worsened in old mice relative to young mice during IAV infection. Aged mice demonstrate more severe changes in gene expression related to memory loss and cognitive dysfunction by IPA. Conclusions These data suggest the genes and pathways related to learning and cognitive performance that were worse at baseline in old mice were further worsened by IAV infection, similar to old patients. Early events in the brain triggered by IAV infection portend downstream neurocognitive pathology in old adults.